DESIGN OF AN INTELLIGENT KEY SYSTEM FOR HOME SECURITY MONITORING: SYARIF'S INTELLIGENT KEY OF DISCOVERY (SITC) MODEL BASED ON ANDROID - SYARIFUDDIN BACO; HUSAIN SYAM; FAISAL SYAFAR (Jurnal Vokasi Keteknikan, 2024)
Objective from This research is to provide convenience while increasing the value of valid and reliable information, results that are in accordance with current conditions in monitoring and responding remotely to the activities of people around (in front of the door) via the Android application. This research was conducted at the elite Citra Garden housing complex, Gowa Regency on Jalan Yusuf Bauti using a questionnaire as a data collection technique. Data obtained from 102 respondents who had filled in and provided an assessment of the statements given were then processed using the SPSS application to carry out validity and reliability tests. The research method used is Research and Development (R&D) as a development using the SDLC (Software Development Life Cycle) software model approach to design a remote monitoring system application for Internet network connections with the stages carried out sequentially from top to bottom, often called the waterfall model or Waterfall model. The result of this research is that it is able to carry out remote monitoring to monitor home security via Android.